A new species of the Gnamptogenys Mordax subgroup (Hymenoptera: Formicidae), with an Identification key to the species within the subgroup - Marcineiro,Frederico S. R. (2020)
Abstract We describe, Gnamptogenys rugimala n. sp, a very distinct new species of the ectatommine genus Gnamptogenys, from specimens collected in forests of southeastern Brazil. We provide some data about G. rugimala n. sp occurrence and ecology as well as a species identification key for the mordax subgroup.